Juvenile pleomorphic adenoma of masticator space: The first case report - Rajat G Panigrahi; Sujit Ranjan Sahoo; Swagatika Panda; Sthitaprajna Lenka; Subrat Kumar Padhiary; Ruchi Bhuyan; Sanat Bhuyan (Wolters Kluwer Medknow Publications, 2013)
Pleomorphic adenoma (PA), also called benign mixed tumor, is the most common tumor of the salivary glands. About 90% of these tumors occur in the parotid gland and 10% in the minor salivary glands. Juvenile PAs are uncommon and about 5-10% of minor salivary gland PA affects patients aged 20 years and under. The most common sites of PA of the minor salivary glands are the palate followed by lips and cheek. Other rare reported sites include the throat, floor of the mouth, tongue, tonsil, pharynx, retromolar area and nasal cavity. The masticator space is a deep facial space with a complex anatomical structure where PA is not known to occur. Here, we report an unusual case of PA of left masticator space in a 16-year-old girl patient, which to the best of our knowledge is the first reported case in English language literature.